Evaluación teórica de la irradiación solar global en el campus matriz de la Universidad Técnica de Cotopaxi - Huaraca Huaraca, Jorge Luis (2022)
At the present study it is intended to estimate global solar irradiation from August 4 to 19 of this year using mathematical models Bristow-Campbell, Hargreaves Samani because in San Felipe sector there was no solar irradiation data, with implementation of Meteorological Station installed in the main campus of Technical University of Cotopaxi there is an imprecision at estimation of solar irradiation on application of mathematical models for obtained data comparison against local station, so it is intended to evaluate theoretically global solar irradiation through the application of mathematical models to determine the approximation of calculated models by experimental method calculated through the use of experimental method, which allows having a solar irradiation data base on sixteen days of August, which will be analyzed with four different dates for a better analysis, concluding that the analyzed samples with reference to Local Station, it is identified that calculated method of greater approximation of solar irradiation corresponds to Hargreaves Samani model with a negligible variation of 6.45%.